PROBLEMS OF ORGANIZATION OF MARKETING RESEARCH IN THE CONVENTION OF THE COVID-19 PANDEMIC - LARKA, Ludmila (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The impact of quarantine restrictions that have affected the specifics of the organization of marketing research is shown. It has been determined that in the context of the COVID-19 pandemic, most marketing research is conducted using Internet technologies. In the conditions of the pandemic, the forms of marketing research have changed. Emphasis is shifting to more active use of Internet marketing opportunities to implement a marketing research plan. Problems of organizing and conducting marketing research are directly related to the management of marketing activities and adaptation of the enterprise to the environment, which is characterized by a high degree of uncertainty. The aim of the article is to study and systematize the key issues of marketing research, taking into account the quarantine restrictions caused by the COVID-19 pandemic. Advantages of remote work with consumers of enterprise products are systematized. The advantages of remote work with consumers are increasing the speed of data processing and interpretation of research results, the possibility of simultaneous work with respondents, the possibility of a more complete geographical coverage of respondents, improving the quality of the questionnaire by adding questions with multimedia components, saving the marketing budget by reducing the cost of marketing research. Relevant types of marketing research are identified, which are most often conducted online. The main types of marketing research conducted with the help of Internet resources are determining the profile of consumers, market research, corporate image research, diagnosing brand value, analysis of consumer satisfaction with the range and parameters of product, evaluating the effectiveness of the advertising campaign, testing of pricing policy, study of the competitive environment of the enterprise. The key problems of organizing and conducting marketing research in a pandemic and formulated ways to solve them are given. In a pandemic, the struggle for the consumer is greatly intensified, so the company's marketing strategies should be as consistent with the overall development strategy, and the timeliness of adjustment of the strategic set is provided by marketing research, which allows diagnosing key changes in consumer behavior in markets.
Keywords: marketing researches; sample; planning; organization; marketing information system; respondent; questionnaire